Differences in Community Composition of Endophytic Fungi Between Above- a Nd Below-Ground Tissues of Aristolochia Chilensis in an Arid Ecosystem - Urzua-Moll, A (BioMed Central Ltd., 2020)
Background: Endophytic fungi are diverse and ubiquitous in nature, yet studies simultaneously comparing endophyte communities in above- A nd below-ground plant tissues are relatively scarce. The main goal of our study was to compare the diversity and community composition of endophytic fungi associated with above- A nd below-ground tissues of the plant Aristolochia chilensis in an arid ecosystem. Endophytic fungi were isolated from healthy leaves and roots of A. chilensis, and the internal transcribed spacer (ITS) region was sequenced for phylogenetic and taxonomic analysis. Results: A combined total of 457 fungal isolates were cultured from leaf and root tissues, belonging to 54 operational taxonomic units (OTUs). The genera Fusarium, Penicillium, Phialemonium and Trichoderma were the most representative endophyte taxa identified in A. chilensis tissues; nevertheless, Fusarium was significantly more dominant in the below-ground community, while foliar endophyte community was dominated by Penicillium. Whereas OTU richness and diversity were not different between below-ground and above-ground tissues, endophyte abundance was on average twice as high in below-ground tissue than in above-ground tissue. Fungal endophyte communities in the two tissue types were significantly dissimilar. Conclusions: Results from this study indicate that A. chilensis harbors a similar diversity of endophytic fungi in above- A nd below-ground tissues. Dominant endophytic fungi were found to be dependent on tissue type, which potentially resulted in marked differences in community structure between above- A nd below-ground tissues. Ecological processes potentially affecting this pattern are discussed. © 2020 The Author(s).